SLAM/SLAM interactions inhibit CD40-induced production of inflammatory cytokines in monocyte-derived dendritic cells - Réthi, Bence (The American Society of Hematology, 2006)
Signaling lymphocyte activation molecule (SLAM, CD150, or SLAMF1) is a self-ligand receptor on the surface of activated T- and B-lymphocytes, macrophages, and dendritic cells (DCs). Here we examine the effect of SLAM/SLAM interactions on CD40L-induced CD40 signaling pathways in human DCs. CD40L-expressing L929 cells induced DCs to produce interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and IL-12, which was strongly inhibited by coexpression of SLAM on the surface of the L929 cells. Similarly, transfection of DCs with SLAM strongly reduced CD40L-induced IL-12 production. Furthermore, the negative effect of SLAM/SLAM interactions on CD40L-induced DC activation was also detected in the presence of lipopolysaccharide (LPS). LPS-induced IL-12 secretion, however, was not inhibited by SLAM engagement. CD40L-activated DCs affected by exposure to SLAM/SLAM engagement were impaired in their ability to induce differentiation of naive T lymphocytes into interferon-γ (IFN-γ)–producing T-helper 1 (Th1) effector cells. These inhibitory effects were not the result of a general unresponsiveness of DCs to CD40L, as SLAM/SLAM interactions did not prevent CD40L-induced up-regulation of CD83, CD86, or human leukocyte antigen (HLA)–DQ on the surface of DCs. Taken together, the results indicate that SLAM/SLAM interactions inhibit CD40-induced signal transduction in monocyte-derived dendritic cells, an effect that was not detectable in earlier studies using anti-SLAM monoclonal antibodies.